2014
DOI: 10.1097/aog.0000000000000228
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin and Antibiotics in Examination-Indicated Cerclage

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 11 publications
0
46
1
Order By: Relevance
“…Subgroup analysis of women who had TVS‐CL < 10 mm, or received tocolytics or antibiotics as additional therapy to cerclage, showed that cerclage may reduce the incidence of PTB; well‐powered trials should be carried out in these groups of patients. Notably, there is evidence in the literature that adjunctive perioperative tocolytics and/or antibiotics might increase the efficacy of the cervical cerclage. Biological plausibility would support these results, as there are several pathways to PTB and these involve mechanical weakness of the cervix from prior surgical procedures or other factors which could be treated with cerclage, infection which could be treated by antibiotics and uterine contractions which could be treated by tocolytics.…”
Section: Discussionmentioning
confidence: 94%
“…Subgroup analysis of women who had TVS‐CL < 10 mm, or received tocolytics or antibiotics as additional therapy to cerclage, showed that cerclage may reduce the incidence of PTB; well‐powered trials should be carried out in these groups of patients. Notably, there is evidence in the literature that adjunctive perioperative tocolytics and/or antibiotics might increase the efficacy of the cervical cerclage. Biological plausibility would support these results, as there are several pathways to PTB and these involve mechanical weakness of the cervix from prior surgical procedures or other factors which could be treated with cerclage, infection which could be treated by antibiotics and uterine contractions which could be treated by tocolytics.…”
Section: Discussionmentioning
confidence: 94%
“…Preterm rupture of membranes, preterm labour and chorioamnionitis were ruled out. Patients were admitted receiving indomethacin to prevent contraction and decrease fetal urine output as a theoretically way to decrease intra-amniotic pressure21 22 as well as ampicillin/sulbactan 1.5 g twice a day as prophylactic antibiotic therapy 21 23…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis published in 2015 (n = 772 women from 11 studies, n = 496 underwent emergency cerclage placement, n = 276 were managed expectantly) found a significant prolongation of pregnancy and reduction of perinatal mortality after placement of an emergency cerclage for cervical dilation (duration of pregnancy: plus 5.4 weeks, perinatal mortality reduced from 58.5 % to 29.1 %) [42]. The administration of indomethacin and cefazolin increased the percentage of women who did not give birth within the following 4 weeks (92.3 vs. 62.5 %) [43].…”
Section: Emergency Cerclagementioning
confidence: 99%